(3aGYdjI HQfGeL ebJQM bGFe Ydi GdJYoqde GdfTW ai JfejI egGQGJ GdJacjQ GdQjGVi h GdMS GdYOOi dOi JdGejP GdeQMdI GdGHJOGFjI ai OhdI GdchjJ (B= s The effectiveness of a program based on active learning in developing mathematical thinking skills and numerical sense at primary school pupils in the state of Kuwait - (3YHOGdYRjR eMeO MeO YGHOs; (3HgjQI Tajb GdQHGW (B: s; (3eMehO CMeO Thb (B: s ((3GdbGgQI (B: s (3YHOGdYRjR eMeO MeO YGHO (B: s, 2015)
(3JgOa GdOQGSI GdMGdjI GdJYQa Ydi aGYdjI HQfGeL ebJQM bGFe Ydi GdJYoqde GdfTW aj JfejI egGQGJ GdJacjQ GdQjGVj h GdMS GdYOOj dOi JdGejP GdeQMdI GdGHJOGFjI aj OhdI GdchjJ(B: (3h JMOjO CSS GdHQfGeL GdebJQM GdbGFe Ydi GdJYoqde GdfTW h GSJQGJjLjGJg(B: (3h JMOjO aGYdjI GdHQfGeL dJfejI egGQGJ GdJacjQ GdQjGVj h GdMS GdYOOi dOi JdGejP GdUa GdNGeS GdGHJOGFj(B: (3h Je GdJWHjb Ydi JdGejP GdUa GdNGeS GdGHJOGFj aj GdaUd GdOQGSj GdKGfj ddYGe GdOQGSj (B2013-2014(3e HeOQSI eMehO Thbj GdCjhHj(B: (3h gj ef eOGQS efWbI GdCMeOi GdJYdjejI(B: (3h GSJNOeJ GdOQGSI GdefgL GdhUaj h GdefgL THg GdJLQjHj s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ h GdHMhK GdJQHhjI (B- (3bSe GdefGgL h WQb GdJOQjSs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJYde GdfTWs; (3GdJacjQ GdQjGVis; (3GdMS GdYOOis